Environmental impact of the subcritical production of silica aerogels. (10th April 2020) - Pinto, Isabel; Silvestre, José D.; de Brito, Jorge; Júlio, Maria F.
Abstract: This study evaluates for the first time the environmental impacts of three different syntheses of subcritical silica aerogels. These aerogels are produced by subcritical drying, a more economical and safer process than that of the supercritical aerogels. The environmental evaluation was performed using the standardised Life Cycle Assessment (LCA) methodology, using a cradle to gate approach. The life cycles of these materials were modelled using production data collected in laboratory and a LCA software. These aerogels are produced to be used as aggregates in wall coating mortars for buildings, conferring them thermal insulating properties. It was concluded that the most critical stages in the LCA of these aerogels are the production of raw materials and the production in the laboratory, the latter mostly due to the high energy consumption. The results presented in this paper correspond to a laboratory-scale production, which makes them expectedly higher than if the aerogels were produced at an industrial scale. It was also found that aerogels obtained using subcritical drying generally lead to lower environmental impacts than supercritical aerogels. Highlights: Environmental impact assessment of silica-based aerogels. Three synthesis methods for subcritically dried silica-based aerogels are compared. The phase of production of raw materials has the greatest environmental importance. The environmental optimization of the process should be done at the drying stage.